Remarkably high and consistent tolerance of a Red Sea coral to acute and chronic thermal stress exposures. Issue 5 (15th February 2021) - Evensen, Nicolas R.; Fine, Maoz; Perna, Gabriela; Voolstra, Christian R.; Barshis, Daniel J.
Abstract: Global warming is resulting in unprecedented levels of coral mortality due to mass bleaching events and, more recently, marine heatwaves, where rapid increases in seawater temperature cause mortality within days. Here, we compare the response of a ubiquitous scleractinian coral, Stylophora pistillata, from the northern Red Sea to acute (7 h) and chronic (7–11 d) thermal stress events that include temperature treatments of 27°C (i.e., the local maximum monthly mean), 29.5°C, 32°C, and 34.5°C, and assess recovery of the corals following exposure. Overall, S. pistillata exhibited remarkably similar responses to acute and chronic thermal stress, responding primarily to the temperature treatment rather than duration or heating rate. Additionally, corals displayed an exceptionally high thermal tolerance, maintaining their physiological performance and suffering little to no loss of algal symbionts or chlorophyll a up to 32°C, before the host suffered from rapid tissue necrosis and mortality at 34.5°C. While there was some variability in physiological response metrics, photosynthetic efficiency measurements (i.e., maximum quantum yield Fv / Fm ) accurately reflected the overall physiological response patterns, with these measurements used to produce the Fv / Fm effective dose (ED50 ) metric as a proxy for the thermal tolerance of corals. This approach produced similar ED50 values for the acute and chronic experiments (34.47°C vs. 33.81°C), highlighting the potential for acute thermal assays with measurements of Fv / Fm as a systematic and standardized approach to quantitively compare the upper thermal limits of reef‐building corals using a portable experimental system.